Preserving Indigenous Papuan Communication Practices in the Era of Globalization: The Kaonak Greeting Tradition - Aulia, Tegar; Hidayat, Sofyan (ENGLISH JOURNAL OF INDRAGIRI, 2026)
In the era of globalization, Western communicative norms increasingly shape global interaction and often overshadow indigenous practices with deep cultural significance. This study examines Kaonak, a traditional Papuan greeting, to explore how indigenous communication systems function as cultural preservation and subtle resistance to homogenization. Using a qualitative ethnographic design, data were gathered from five indigenous Papuans in Jayapura through interviews, participant observations, and field notes, then analyzed using Miles and Huberman’s interactive model. The findings show that Kaonak embodies the Papuan philosophy of basodara (brotherhood), expressing unity, respect, and relational harmony. Although modernization has reduced its use among younger generations, the greeting remains meaningful for those who view it as cultural heritage. Its continued practice reflects an assertion of identity and a moral worldview rooted in Papuan cosmology. The study argues that sustaining Kaonak contributes to cultural resilience and highlights the importance of integrating indigenous communicative traditions into educational and intercultural programs.